Influence of the fixation point of the artificial popliteal muscle graft on the stability of the knee joint under external rotational load - Panchenko, S.; Golovakha, M. L.; Kolosov, D.; Onyshchenko, S.; Zub, T.; Chechel, T.; Головаха, Максим Леонідович (My University, 2022)
This paper investigated the dependence of the stability of the knee joint, when exposed to external rotational load on the lower leg, on the position of the graft of the tendon of the popliteal muscle. Estimation finite-element models of the right knee joint of an adult were constructed, which included the articular ends of the bones that form this joint, as well as its main ligaments. The models reflected a surgery to restore posterolateral angle structures and differed only in the position of the popliteal tendon graft. That position was set by the point of attachment of the graft to the posterior surface of the tibia. At the same time, the fixation point changed both vertically and horizontally, in the frontal plane. In addition, a control model was built in which the hamstring tendon was completely absent. As a result of the calculations, patterns of the distribution of the fields of movement of the points of the finite-element model were obtained. As criteria for assessing the effectiveness of the selected position of the graft, movements of the lower leg model in the horizontal plane were proposed. Analysis of the results of the calculations showed that the greatest movements in all directions were obtained in the control model, in which the hamstring of the popliteal muscle was absent. The magnitudes of the considered movements derived from the control model exceeded the same values in the model with minimal movements by 17, 37, 17, 32, and 16 %. From the point of view of the stability of the tibia under rotational load, the most effective was the fixation of the graft on the posterior surface of the tibia as laterally as possible and closer to its articular surface. This is indicated by the magnitude of the movements, which, in this case, turned out to be the smallest in all directions
Keywords: knee joint; hamstring tendon; external rotational load; graft; finite-element model; stiffness characteristics